Monocytosis and a Low Lymphocyte to Monocyte Ratio Are Effective Biomarkers of Ulcerative Colitis Disease Activity. Issue 8 (August 2015) - Cherfane, Cynthia E.; Gessel, Luke; Cirillo, Dominic; Zimmerman, Miriam B.; Polyak, Steven
Abstract : Background: Current biomarkers in ulcerative colitis (UC) are limited by their performance, cost, and limited availability in daily practice. This study examined alterations in the leukocyte profiles as biomarkers of UC activity, including the effects of age, gender, and medications. Methods: Case–control study that included 110 UC subjects, 75 subjects with Clostridium difficile infection, and 75 non-inflammatory bowel disease (IBD) subjects, randomly selected from a single-institution IBD database. Mean values of neutrophils (N), lymphocytes (L), monocytes (M) and their ratios were compared between groups. Receiver operator curve analyses assessed the performance of each biomarker in discriminating disease states. Subgroup analyses examined leukocytes profiles with endoscopic activity. Results: Elevated monocyte counts and decreased L/M values significantly differed between subjects with active UC and UC in remission and performed better than the other leukocyte profiles. A monocyte count of 483 and L/M ratio of 3.1 were 60% sensitive and had a specificity of 61% and 53%, respectively for active UC. Monocyte count >860 and L/M value <1.6 had a 75% positive predictive value for UC activity. Those markers also correlated with endoscopically active disease. L/M and N/L values performed best at differentiating active UC from non-IBD controls, whereas N/L and N values performed best at differentiating from C. difficile controls. Conclusions: Monocytosis and a low L/M ratio might be effective, readily available, and low-cost biomarkers to identify disease activity in UC patients. N/L values were more effective in distinguishing active UC patients from patients without IBD and those with C. difficile infection. Abstract : Article first published online 19 May 2015Supplemental Digital Content is Available in the Text.